2011
DOI: 10.1186/1475-2840-10-92
|View full text |Cite
|
Sign up to set email alerts
|

Effects of granulocyte-colony stimulating factor (G-CSF) on diabetic cardiomyopathy in Otsuka Long-Evans Tokushima Fatty rats

Abstract: BackgroundDiabetic cardiomyopathy (CMP) is a common and disabling disease in diabetic patients, however no effective treatments have been developed. Although granulocyte-colony stimulating factor (G-CSF) improves heart function in myocardial infarction, its effect on non-ischemic CMP such as diabetic CMP is unknown. In the present study, we investigated the effects of G-CSF on diabetic CMP in a rat model of type II diabetes.MethodsTwenty 7-week-old male Otsuka Long-Evans Tokushima Fatty (OLETF: a rat model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Furthermore, adiponectin supplementation improved concentric cardiac hypertrophy in adiponectin-deficient mice [9]. Recent study showed that recombinant human granulocyte-colony stimulating factor (G-CSF) ameliorates cardiac diastolic dysfunction and fibrosis in OLETF rats [47]. Although cardiac hypertrophy was not detected in the OLETF rat model used in this study, recent study showed that ALA (100 mg/kg/day) reversed impairment of systolic function in STZ-treated diabetic rats compared to controls [21].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, adiponectin supplementation improved concentric cardiac hypertrophy in adiponectin-deficient mice [9]. Recent study showed that recombinant human granulocyte-colony stimulating factor (G-CSF) ameliorates cardiac diastolic dysfunction and fibrosis in OLETF rats [47]. Although cardiac hypertrophy was not detected in the OLETF rat model used in this study, recent study showed that ALA (100 mg/kg/day) reversed impairment of systolic function in STZ-treated diabetic rats compared to controls [21].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines and growth factors could be used to potentiate stem cell mobilization and homing to the myocardium. Improved mobilization with granulocyte colony-stimulating factor (G-CSF) ameliorates the rat model of CDM decreasing perivascular interstitial fibrosis [ 37 ]. Our recent study in BM cells from infarcted patients demonstrated that SDF-1 directed migration enriches for cells with increased healing activity [ 38 ].…”
Section: The Upside: Evidence For Bm-derived Stem Cells Improving Diamentioning
confidence: 99%
“…For example, one study showed that G-CSF increased angiogenesis and reversed ischemic damage in the brain [8]. In other studies, G-CSF protected against renal tubular injury induced by adriamycin [9] and against hepatic steatosis [10], as well as diabetic cardiomyopathy in rats [11]. Flaquer M, et al demonstrated that the combination of hepatocyte growth factor gene therapy with hematopoietic stem cell mobilization by G-CSF may contribute to renal tissue repair and regeneration in diabetes- induced mice [12].…”
Section: Introductionmentioning
confidence: 99%